Artificial hybrids of influenza A virus RNA polymerase reveal PA subunit modulates its thermal sensitivity. - Takahito Kashiwagi (PLoS ONE, 2010)
BACKGROUND: Influenza A virus can infect a variety of different hosts and therefore has to adapt to different host temperatures for its efficient viral replication. Influenza virus codes for an RNA polymerase of 3 subunits: PB1, PB2 and PA. It is well known that the PB2 subunit is involved in temperature sensitivity, such as cold adaptation. On the other hand the role of the PA subunit in thermal sensitivity is still poorly understood. METHODOLOGY/PRINCIPAL FINDINGS: To test which polymerase subunit(s) were involved in thermal stress we reconstituted artificial hybrids of influenza RNA polymerase in ribonucleoprotein (RNP) complexes and measured steady-state levels of mRNA, cRNA and vRNA at different temperatures. The PA subunit was involved in modulating RNP activity under thermal stress. Residue 114 of the PA subunit was an important determinant of this activity. CONCLUSIONS/SIGNIFICANCE: These findings suggested that influenza A virus may acquire an RNA polymerase adapted to different body temperatures of the host by reassortment of the RNA polymerase genes.